Menakar Pembaharuan Pendidikan Muhammad Abduh - Muhammad Nasihuddin (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2020)
Muhammad Abduh is a figure of 19th-century Islamic reformer who promotes religious rationality. As a reformer, Muhammad ‘Abduh views education as an important element for the Islamic community to regain its long-lost dignity. Muhammad ‘Abduh wanted to play a role in the revival of the civilization of the people who were being hit by the storm of backwardness. He saw that the road to that was "education", but not every education, but education based on Islamic religious references. Among contemporary intellectuals, he is known as a modernist scholar. One of his characteristics, he dares to reject the dichotomy of science. This is consistent with the assumption that Muhammad Abduh did not reject the system offered by the western education system to be used as a chain of curricula applied in Islamic tertiary institutions. Muhammad ‘Abduh's thought about education was considered to have had a positive influence on Islamic educational institutions so that it was considered as the beginning of the rise of Islamic Education at the beginning of the 20th century. Keywords : education, reform